Clinical Trial of Emepronium Bromide in Nocturnal Frequency of Old Age. Issue 5651 (26th April 1969) - Brocklehurst, J. C.; Dillane, J. B.; Fry, John; Armitage, P.
Abstract : A double-blind cross-over trial of emepronium bromide (Cetiprin) in nocturnal frequency of micturition in a group of elderly women living in their homes showed that the drug was superior to placebo in diminishing urinary frequency, though not every person benefited. It is suggested that the drug may alter the established habit of rising at night to pass urine. Side-effects were negligible.